A Comparative Study of Selected Psychological Variables between High and Low Performer of Football Inter University Players (International Journal of Food and Nutritional Sciences, 2022)
After many researches on psychology, it was found that psychology is the study of human behavior. In other words we can say that psychological factors affect the human thinking powers and the same thing is also applied on sports also. The present study was based on psychological factors i.e. stress, aggression and anxiety. The purpose of this study was to find out the difference between high and low performer of football Interuniversity player in relation to stress, aggression and anxiety. Total 192 Inter university Football players were randomly selected as sample and their age was between 18 to 25years. Three standardized questionnaires for stress, aggression and anxiety were used for the collection of data. The data was analyzed by statistical technique ‘t’ test which was significant at 0.05 level. In the findings of the study it was found that there was no significant statistical difference between high and low performer in relation to stress and aggression level of Football Interuniversity players whereas there was significant statistical difference found between high and low performer in relation to anxiety level of Football Interuniversity players.